Protection For Work Accidents And Occupational Diseases During The Covid-19 Pandemic - Ansyori, Ahmad; Khakim, Abdul (Operations Research: International Conference Series, 2023)
Employment sosial security is a basic right of workers/laborers whose fulfillment must be guaranteed by the state in order to realize the welfare of workers/laborers and their family members. In addition, sosial security as a sosial protection system not only reduces poverty but also protects people from falling into poverty (Haiyani, 2022). Indonesia already has Law Number 40 of 2004 concerning the National Sosial Security System (UU 40/2004) and Law Number 24 of 2011 concerning Sosial Security Administering Bodies (UU 24/2011). One of the rights of workers is to get work accident insurance if they have an accident related to their work. However, what if the worker is exposed to COVID-19 at work? what if when you are hospitalized due to a work accident, you are exposed to COVID-19?. This paper is intended to analyze the need and different arrangements for the Obligations and Rights of workers in the event of having a work accident during the COVID-19 pandemic, which has not been regulated in Law Number 24 of 2011 concerning the Sosial Security Administering Body (Law No.24/2011), which is a public legal entity that has the authority as well as the obligation to implement employment social security. This research uses normative juridical research methods.Â